Pengaruh Kepemimpinan dan Budaya Organisasi terhadap Kinerja Karyawan - Syamsu Nurkarim (Departement of Mathematics Education, 2023)
The performance of employees has a considerable impact on the success of an organisation. In businesses where the main source of income is derived from profits (as is the case with most commercial enterprises), the aim is to make as much money as possible. The primary goal of Indonesia's development in the field of human resources today is to create a society of high-quality human resources and a prosperous Indonesia. This is done in recognition of the importance of continuously improving the quality of human resources, which requires that every individual and group be able to improve their performance. The purpose of this study is to investigate the effect of Leadership Style and Organizational Culture on Employee Performance at PT Swadharma Sarana Informatika. The population is made up of 102 people with a sample of water. The research results showed that leadership had a positive and significant effect of 0.864, which means that leadership style affected employee performance but was not significant. The culture of an organization is significant in that it has a positive and significant impact on employee performance. At the same time, leadership style and organizational culture have a positive and significant impact on employee performance. The findings of this research suggest that the leadership style at PT Swadharma Sarana Informatika should be adapted to the current situation and conditions.